Parentesco, mito y territorio entre los aido pai (Secoya) de la Amazonía peruana - Casanova Velásquez, Jorge (2005)
This paper presents the ancestral territory of a native group in the Peruvian forest, the Aido Pai. Based on his field work, the author explores the relation between kinship, myth and habitat. With this support, the author gives criteria for a legal and just adjudication of territory to the Aido Pai, when the National Park of Gueppi is created in the region of upper Putumayo.